Diferenças funcionais entre longevos da capital e do interior do Rio Grande do Sul - Macedo, Eléia de (2018)
The functionality is directly related to the capacity of autonomy and independence in the accomplishment of daily activities. Evaluating oldest-old subjects (80 years and older) functionality is essential to identify difficulties and facilities in the implementation of the Daily Life Activities and possible differences between the oldest-old residents in different urban areas. The objective is to correlate the self-perception of functionality with the functional performance tests in order to understand possible differences in the functional evaluation of residents living in the capital and in the interior. It is a cross-sectional study with oldest-old people, of both sexes. The data collection was carried out in three moments and in different locations, defined as: Capital (Porto Alegre-RS) and Interior (Galópolis- RS and Cambará do Sul- RS). Oldest-old were interviewed from the AFASII questionnaire translated and adapted from the "Health ABC Study", after performing the functional performance tests for upper and lower limbs (Manual Grip Test, Sit Test, Chair Lift and Timed Test Up and Go). A baropodometric platform, the Zeno Walkway System®, was used to evaluate gait performance. The data were analyzed by the Epi Info Program® 7.1.3 and Linear Regression was used to test the correlation between the variables. In this study 102 oldest-old subjects were evaluated, with a mean age of 84.6 years. Among the cities, there was no significant difference in the distribution by gender and age averages. The Timed Up and Go test (TUG) presented better performance in the oldest-old resident in the Capital (p <0.001), while manual grip strength was higher in the in-dwelling oldest-old, but not significant. The AFASII instrument proved to be a sensitive instrument for evaluating the self-perception of functionality. Based on the tests used, the results show that the oldest-old residents of the rural area are more easily able to perform the activities of the upper limbs, while the long-lived residents of the capital have an more easier performance of the lower limbs.